2014
DOI: 10.1161/circresaha.114.302590
|View full text |Cite
|
Sign up to set email alerts
|

High-Resolution Imaging of Intravascular Atherogenic Inflammation in Live Mice

Abstract: Rationale:The inflammatory processes that initiate and propagate atherosclerosis remain poorly understood, largely because defining the intravascular behavior of immune cells has been technically challenging. Respiratory and pulsatile movements have hampered in vivo visualization of leukocyte accumulation in athero-prone arteries at resolutions achieved in other tissues.Objective: To establish and to validate a method that allows high-resolution imaging of inflammatory leukocytes and platelets within the carot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
83
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
4

Relationship

3
6

Authors

Journals

citations
Cited by 75 publications
(86 citation statements)
references
References 42 publications
3
83
0
Order By: Relevance
“…LysM is expressed in all myeloid cells including macrophages, monocytes, and granulocytes but also in AMCs, which possess similarities to the myeloid linage. 40,41 Tissue-resident myeloid cells as well as progenitor cells are present in healthy vessels and in part are LysM positive. [42][43][44][45] The deletion experiments in the present study indicate that potentially tissue-resident, adventitial-localized, clodronate-sensitive macrophages are the source of SDF1 in response to injury and 1,25-VitD3.…”
Section: Discussionmentioning
confidence: 99%
“…LysM is expressed in all myeloid cells including macrophages, monocytes, and granulocytes but also in AMCs, which possess similarities to the myeloid linage. 40,41 Tissue-resident myeloid cells as well as progenitor cells are present in healthy vessels and in part are LysM positive. [42][43][44][45] The deletion experiments in the present study indicate that potentially tissue-resident, adventitial-localized, clodronate-sensitive macrophages are the source of SDF1 in response to injury and 1,25-VitD3.…”
Section: Discussionmentioning
confidence: 99%
“…This implies a transluminal route for the accession of these cells to early sites of atherosclerosis where they promote monocyte recruitment and lesion development. 20,25 At a similar stage of disease, neutrophil extracellular traps were found at the bifurcation sites of carotid arteries in vivo but not in healthy mice. 26 The potential contribution of dendritic cells has been established in CC chemokine ligand 17 (CCL17) E/+ Apoe −/− mice where CCL17-expressing dendritic cells were shown to accumulate in the lesion and to interact with T-cells, thereby promoting atherogenesis.…”
Section: Tplsm In Atherosclerotic Researchmentioning
confidence: 99%
“…Image acquisition triggered on respiratory/ heart cycles, mechanical stabilization, and strong fluorescent markers enabled recording of good quality time-lapse movies of the arterial wall and leukocyte interactions with the vessel wall, 17 even in 3D ( Figure 1B). 20 Using a comparable layout, Li et al 21 managed to track single leukocytes recruited to damaged cardiac tissue in living mice after coronary ischemia reperfusion, both in transplanted and in native hearts, ≤120-μm depth. More recently, an intravital live cell-triggered imaging system has been developed by Ley et al 22 to reveal monocyte patrolling and macrophage migration in atherosclerotic arteries, implementing cardiac triggered acquisition, as well as frame selection and image registration algorithms, to produce stable movies of myeloid cell movement in atherosclerotic arteries in live mice.…”
Section: Tplsm In Atherosclerotic Researchmentioning
confidence: 99%
“…Several studies have shown that platelets and myeloid leukocytes display reciprocal cooperation for recruitment into the inflamed vasculature; for example, neutrophils recruited to TNF-α-stimulated venules efficiently capture circulating platelets, 14 and this has been recently demonstrated to also occur in nascent atherosclerotic lesions. 15 In turn, activated platelets can secrete and deposit chemokines on the surface of leukocytes and endothelial cells, thereby enhancing adhesion of the leukocytes on atherosclerotic surfaces. 7 In agreement with these previous studies, Karshovska et al show that JAM A-deficient platelets release more CXCL4 and CCL5-2 potent inflammatory chemokines-into the plasma, thereby creating a proatherogenic milieu that facilitates their own deposition and further recruitment of monocytes and neutrophils onto atherosclerotic regions of arteries.…”
Section: Circulation Research February 13 2015mentioning
confidence: 99%